REPRESENTASI POLIGAMI DALAM FILM SURGA YANG TAK DIRINDUKAN KARYA KUNTZ AGUS ( STUDI SEMIOTIKA ROLAND BARTHES) - Mhd Dandy Alexander J.A; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Poligamy pheomenon which is popular in society makes poligamy being such a controversion. There are some support it and some part against it. Based on poligamy phenomenon which is emerge in mass media generally, and in film especially, make some interpretation of poligamy in film “Surga yang Tak Dirindukan”. A discourse about poligamy which is popular since the release of film “Surga yang Tak Dirindukan” attract researcher to find the meaning and messsages that showed audio and visually. Then, this research aimed to know how is the representation of poligamy in film “Surga yang Tak Dirindukan”.This research use descriptive qualitative method then analyzed by semiothics Roland Barthes’s model. Data collecting technique that used in this research is observing audio and visual presentation in film “Surga yang Tak Dirindukan”, documentation and interview by using purposive sampling.The result shows that there are poligamy representation in film “Surga yang Tak Dirindukan”. This film tell about a woman that struggle applying the meaning of sincere and patient in her life for intact of her household. Sincere and patient in this film can take as a learning life. When we face a hard problem, then we must sincere and patient, because when we applied them, we can find a better solution.